A new α-pyrone from the mangrove endophytic fungus Phomopsis sp. HNY29-2B. Issue 2 (17th January 2017) - Cai, Runlin; Chen, Senhua; Liu, Zhaoming; Tan, Chunbing; Huang, Xishan; She, Zhigang
Abstract: A new α -pyrone derivative, phomopyrone A (1 ), together with two known compounds (2 –3 ), was isolated from the culture of the mangrove endophytic fungus Phomopsis sp. HNY29-2B. Their structures were determined by detailed analysis of spectroscopic data. The configuration of1 was further confirmed by X-ray diffraction. All isolated compounds were evaluated for antibacterial and antioxidative activities. Compound2 exhibited antibacterial activities with minimal inhibition concentration (MIC) values of 25 and 50 μM against Bacillus subtilis and Pseudomonas aeruginosa, and compound3 showed activities against Staphylococcus aureus and B. subtilis with MIC values of 25 and 50 μM, respectively. Abstract :